Research on sEMG Pattern Recognition Algorithm and Implementation of a Gesture Recognition System - Tian, Yuepeng; Zhang, Zhimin; Li, Yuwen (2023 International Conference on Sensing, Measurement & Data Analytics in the era of Artificial Intelligence (ICSMD), 2023)
Pattern recognition of surface electromyogram (surface EMG, sEMG) signals can obtain human movement information. In recent years, this technology has been widely used in many fields. In the algorithm part, this paper proposes a model based on Convolutional Neural Network (CNN) and Recurrent Neural Network (RNN). The effects of different algorithm structures and parameter selections are compared. On this basis, Depthwise separable convolution is introduced to reduce the number of parameters while maintaining high accuracy. In addition, the attention module SElayer is introduced to further improve the performance of the algorithm. The final algorithm achieved an accuracy rate of 93.41% on the NinaPro-DB2 dataset. In addition to the algorithm, this paper also builds a sEMG gesture recognition system with the help of an embedded platform. The system is mainly composed of an 8channel sEMG acquisition board and a computer, and includes four functional modules: data acquisition and annotation, data preprocessing, model training and real-time classification. Finally, the system collected sEMG data from 7 subjects. The model achieved good results on the dataset and completed the real-time classification.